The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/masy.201600029
|View full text |Cite
|
Sign up to set email alerts
|

Production and Functionalization of P(MMA‐co‐AA) Nanoparticles by Miniemulsion Polymerization

Abstract: Summary In the present work, the production of poly(methyl methacrylate‐co‐acrylic acid), P(MMA‐co‐AA), nanoparticles and the subsequent functionalization through immobilization of BSA (bovine serum albuminum) and lysine were investigated. Nanoparticles produced presented average size of 100 nm, zeta potential of −40 mV and AA content ranging from 1 to 10 mol%. Particularly, it was shown that inespecific physical interactions control the adsorption of BSA onto the particle surfaces. On the other hand, lysine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These concentrations were defined in accordance with previous MMA miniemulsion polymerization studies. [8,16,29,30] The initial miniemulsions were prepared with a sonifier (Branson 450, Marshall Scintific, Hampton, USA) at 160 W for 5 min or with an ultra-turrax (T10 basic, IKA, Staufen, Germany) for 5 min at 14,500 rpm, using an ice bath to control the temperature of the emulsified system and keep it close to room temperature. The polymerizations were conducted in a 100 mL glass reactor (EasyMax 102, Mettler Toledo, Ohio, USA) at 80 o C under the agitation of 500 rpm for 180 min.…”
Section: Polymerization Reactionsmentioning
confidence: 99%
“…These concentrations were defined in accordance with previous MMA miniemulsion polymerization studies. [8,16,29,30] The initial miniemulsions were prepared with a sonifier (Branson 450, Marshall Scintific, Hampton, USA) at 160 W for 5 min or with an ultra-turrax (T10 basic, IKA, Staufen, Germany) for 5 min at 14,500 rpm, using an ice bath to control the temperature of the emulsified system and keep it close to room temperature. The polymerizations were conducted in a 100 mL glass reactor (EasyMax 102, Mettler Toledo, Ohio, USA) at 80 o C under the agitation of 500 rpm for 180 min.…”
Section: Polymerization Reactionsmentioning
confidence: 99%
“…[5,24,25] Miniemulsion polymerizations have been used extensively for manufacture of polymer nanoparticles. [26][27][28] This technique presents many competitive advantages, including the fact that use of toxic solvents is not necessary, the high stability of obtained polymer latex and the possibility to perform the encapsulation of chemicals in situ. A typical formulation comprises two phases: the dispersant aqueous phase and the emulsified organic phase, which contains monomers and co-stabilizers.…”
mentioning
confidence: 99%
“…First of all, it is important to emphasize that previous works investigated the manufacture of P(MMA‐co‐AA) nanoparticles at distinct conditions and using different AA concentrations,29,38 reporting the copolymer compositions (obtained through nuclear magnetic resonance analyses) and molar mass distributions (obtained through gel permeation chromatography) of the obtained nanoparticles. Besides, scanning electron microscopy (SEM) analyses of the obtained P(MMA‐co‐AA) nanoparticles showed that the obtained particles were spherical, with average sizes of 100 nm and presenting very narrow size distributions 32. According to the recipe presented in Table 1, the final AA content of the obtained copolymer was equal to 1 mol% and the weight‐average molar mass was equal to 1.3 × 10 3 kg mol −1 , with polydispersity of 2.0, as also reported previously.…”
Section: Resultsmentioning
confidence: 99%